Sulfur cathode
By using a sulfur cathode of high-surface charge anionic functionalized cellulose nanofibers in lithium-sulfur batteries, the problems of sulfur insulation characteristics, polysulfide shuttle effect and volume expansion in lithium-sulfur battery production are solved, and efficient lithium ion transport and high energy density are achieved.
Patent Information
- Application Number
- CN202380052956.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-23
- Filing Date
- 2023-06-23
- Publication Date
- 2025-03-04
AI Technical Summary
The production of existing lithium-sulfur batteries is hindered by problems such as the inherent insulation properties of sulfur, the "shuttle effect" of polysulfides, and the volume expansion of the sulfur cathode during operation.
A sulfur cathode containing anionically functionalized cellulose nanofibers with high surface charges are used to form a sulfur cathode with high ionic conductivity and conductivity by mixing with sulfur-containing materials and conductive materials.
The high ion conductivity and electrical conductivity of the sulfur cathode are achieved, the transportation of polysulfide ions is reduced, the transportation of lithium ions is promoted, and the weight energy density and volume energy density of lithium sulfur batteries are improved.
Smart Images

Figure CN119563240A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a sulfur cathode and a lithium sulfur battery incorporating the same. The sulfur cathode contains anion-functionalized cellulose nanofibers that exhibit a high surface charge. Background Art
[0002] Lithium-sulfur (Li-S) batteries offer many potential advantages over lithium-ion (Li-ion) battery technology, including improved gravimetric energy density, reduced raw material costs due to the lower cost of sulfur than the transition metals employed in Li-ion systems, and reduced environmental impact of the battery cell materials.
[0003] However, the production of viable Li-S cells has been hampered by a number of issues, including the intrinsic insulating properties of sulfur, the so-called polysulfide "shuttle effect," in which polysulfides dissolve in the electrolyte resulting in sulfur loss from the cathode, and volume expansion of the sulfur cathode during operation.
[0004] Therefore, there remains a need to provide a sulfur cathode that addresses one or more of these issues. The present disclosure is relevant to this need.
[0005] The reference to any prior art in this specification does not constitute an acknowledgement or implication that this prior art forms part of the common general knowledge in any jurisdiction, nor does it mean that this prior art can be reasonably understood by a person skilled in the art, regarded as related to and / or combined with other prior art. Summary of the invention
[0006] In one aspect, the present disclosure provides a sulfur cathode comprising:
[0007] a) a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers;
[0008] b) one or more sulfur-containing materials; and
[0009] c) One or more conductive materials.
[0010] In an embodiment, the sulfur cathode comprises:
[0011] a) about 2 wt.% to about 20 wt.% of a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers;
[0012] b) from about 60 wt.% to about 80 wt.% of one or more sulfur-containing materials; and
[0013] c) from about 10 wt. % to about 30 wt. % of one or more conductive materials.
[0014] In an embodiment, the sulfur cathode comprises:
[0015] a) about 5 wt.% to about 15 wt.% of a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers;
[0016] b) from about 65 wt.% to about 75 wt.% of one or more sulfur-containing materials; and
[0017] c) from about 15 wt. % to about 25 wt. % of one or more conductive materials.
[0018] In an embodiment, the plurality of anionically functionalized cellulose nanofibers have one or more of the following properties:
[0019] a) a fibril diameter of about 0.1 nm to about 20 nm;
[0020] b) a fibril length of about 20 nm to about 1000 nm;
[0021] c) a fibril aspect ratio of about 10 to about 1000; and
[0022] d) The zeta potential is more negative than about -60 mV.
[0023] In an embodiment, the one or more sulfur-containing materials include one or more of elemental sulfur, Li2S, and MoS2.
[0024] In an embodiment, the one or more conductive materials include one or more of: carbon black, graphite, graphene, activated carbon, carbon nanotubes, and carbon fibers.
[0025] In embodiments, the cathode has a porosity of less than about 50% or less than about 40%.
[0026] In an embodiment, the cathode has an arithmetic surface roughness of less than about 25 μm.
[0027] In embodiments, transport of polysulfide anions within the cathode is hindered relative to a sulfur cathode in the absence of the cellulose composition disclosed herein.
[0028] In embodiments, lithium ion transport within the cathode is facilitated relative to a sulfur cathode in the absence of the cellulose composition disclosed herein.
[0029] In another aspect, the present disclosure provides a lithium-sulfur battery comprising a lithium anode, a separator, a cathode according to any one of the embodiments disclosed herein, and an electrolyte disposed between the anode and the cathode.
[0030] In an embodiment, the ratio of electrolyte volume to sulfur weight in the lithium-sulfur battery is less than about 6.0 μl / mg.
[0031] In an embodiment, the ratio of electrolyte volume to sulfur weight in the lithium-sulfur battery is about 3.5 μl / mg to about 5.0 μl / mg.
[0032] The sulfur cathode can facilitate transport of lithium ions across the cathode during charge or discharge.
[0033] The sulfur cathode can hinder the transport of polysulfide ions across the cathode during charge or discharge.
[0034] In embodiments, the plurality of anionically functionalized cellulose nanofibers have a fibril diameter of about 0.5 nm to about 10 nm, or about 1 nm to about 6 nm, or about 2 nm to about 4 nm.
[0035] In embodiments, the plurality of anionically functionalized cellulose nanofibers have a fibril length of about 40 nm to about 700 nm, or about 70 nm to about 500 nm, or about 100 nm to about 400 nm.
[0036] In embodiments, the plurality of anionically functionalized cellulose nanofibers have a fibril aspect ratio of about 15 to about 750, or about 20 to about 500, or about 25 to about 200.
[0037] In embodiments, the plurality of anionically functionalized cellulose nanofibers has a zeta potential of about -60 mV to about -90 mV.
[0038] In embodiments, the plurality of anionically functionalized cellulose nanofibers are functionalized with one or more of: carboxyl, phosphonate, sulfonate, sulfate, hydroxyl, nitrate, and carbonate.
[0039] In embodiments, the plurality of anionically functionalized cellulose nanofibers comprises greater than 1 mmol anionic groups per gram of nanofibers or greater than 1.5 mmol anionic groups per gram of nanofibers.
[0040] In embodiments, the plurality of anionically functionalized cellulose nanofibers comprises about 1 mmol to about 4 mmol anionic groups per gram of nanofibers, or about 1.5 mmol to about 4 mmol anionic groups per gram of nanofibers, or about 2 mmol to about 4 mmol anionic groups per gram of nanofibers.
[0041] In an embodiment, the plurality of anionically functionalized cellulose nanofibers are functionalized to have carboxyl groups.
[0042] In another aspect, the present disclosure provides a cathode slurry composition comprising:
[0043] a) a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers;
[0044] b) one or more sulfur-containing materials;
[0045] c) one or more conductive materials; and
[0046] d) Water.
[0047] In embodiments, the ratio of water to the combined weight of components a), b), and c) is from about 1 ml / g to about 40 ml / g or from about 3 ml / g to about 30 ml / g.
[0048] In the examples, when measured in the temperature range of 20-25°C, 3 ml / g of the slurry has a -1 The viscosity at the shear rate is greater than about 1000 Pa.s.
[0049] In another aspect, the present disclosure provides a method for preparing a cathode slurry composition according to any one of the embodiments disclosed herein, the method comprising the steps of mixing a cellulose composition, one or more sulfur-containing materials, one or more conductive materials, and water, wherein the cellulose composition comprises a plurality of anion-functionalized cellulose nanofibers.
[0050] In an embodiment of the method, the cellulosic composition, the one or more sulfur-containing materials, and the one or more conductive materials are dry mixed prior to mixing with water.
[0051] In another aspect, the present disclosure provides a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers having one or more of the following properties:
[0052] a) a fibril diameter of about 0.1 nm to about 20 nm;
[0053] b) a fibril length of about 20 nm to about 1000 nm;
[0054] c) a fibril aspect ratio of about 10 to about 1000; and
[0055] d) The zeta potential is more negative than about -60 mV.
[0056] In another aspect, the present disclosure provides a method for preparing a cellulose composition according to any one of the embodiments disclosed herein, the method comprising:
[0057] a) treating a cellulose source with one or more agents capable of anionically functionalizing cellulose nanofibers; and
[0058] b) subjecting the anionically functionalized cellulose nanofibers to shear conditions to reduce one or more fibril sizes.
[0059] In embodiments, the shear conditions comprise agitating the aqueous mixture of anionically functionalized cellulose nanofibers.
[0060] In an embodiment, the shearing condition comprises one or both of ultrasonic homogenization and high pressure homogenization of the aqueous mixture of the anionically functionalized cellulose nanofibers.
[0061] Advantages of the presently disclosed sulfur cathodes and batteries comprising the same include one or more of the following:
[0062] ● The sulfur cathode has high ionic conductivity and electrical conductivity;
[0063] The porosity of the sulfur cathode is relatively low;
[0064] The sulfur cathode has a relatively smooth surface;
[0065] The sulfur cathode has a favorable transport effect, promoting Li ion transport but hindering polysulfide ion transport;
[0066] ● The sulfur cathode slurry has rheological properties that facilitate processing;
[0067] • Batteries employing the sulfur cathode exhibit high gravimetric and volumetric energy densities.
[0068] Unless explicitly stated otherwise, any embodiment herein should be considered applicable to any other embodiment mutatis mutandis.
[0069] The scope of the present disclosure is not to be limited by the specific embodiments described herein, which are provided for illustrative purposes only. As described herein, functionally equivalent products, compositions and methods are clearly within the scope of the present disclosure.
[0070] Further aspects of the disclosure and further embodiments of the aspects described in the preceding paragraphs will become apparent from the following description, which is given by way of example and with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1Polarized light microscopy images of cellulose nanofibers (CNFs) and sulfur cathodes; (a) Pol-Scope image of native CNFs showing thick and long fibers (scale 100 μm); (b) Pol-Scope image of carboxylated CNFs showing separated and short fibers resulting from further TEMPO oxidation; Pol-Scope images of (c) native CNF cathodes; (d) carboxylated CNF cathodes; (e) to (g) carboxylated CNF cathodes at concentrations of 3.3 mg / ml, 33.3 mg / ml and 333.3 mg / ml, respectively.
[0072] Figure 2 Characterization of CNFs with different surface charges is shown; (a) the apparent zeta potential comparison between different carboxylated CNF samples and CMC (carboxymethyl cellulose), which provides evidence of high surface charged carboxylated CNFs that can prevent aggregation and facilitate ion mobility; (b) steady-state shear flow behavior; (c) contact angle measurements of electrolyte droplets on carboxylated CNF films; (d) ionic conductivity measured by AC impedance technique.
[0073] Figure 3 The morphological and microstructural studies of the sulfur cathode are shown; (a) CMC cathode profilometer inspection; (b) and (c) top-down SEM images of the CMC cathode at 50 μm and 1 μm scales, respectively; (d) carboxylated CNF cathode profilometer inspection; (e) to (i) top-down SEM images of the carboxylated CNF cathode at 50 μm, 1 μm, 200 nm, 500 nm and 200 nm scales; (j) schematic illustration of the carboxylated CNF skeleton; (k) to (m) cross-sectional SEM images of the carboxylated CNF cathode at 10 μm, 1 μm and 200 nm scales, respectively.
[0074] Figure 4 Shown are (a) schematic illustration of the EBAC test; (b) comparison of EBAC current between CMC (lower trace) cathode and carboxylated CNF (upper trace) cathode; (c) cross-sectional SEM images of CMC thick cathode (20 μm scale) and (d) carboxylated CNF thick cathode (20 μm scale); (e) EBAC treatment images of CMC thick cathode and (f) carboxylated CNF thick cathode.
[0075] Figure 5 The coin cell-level cycling performance of carboxylated CNF cathodes is shown; (a) sulfur loading is about 1 mg cm -2The four data curves across the middle of the figure show CNF2, CNF1.5, CNF1.4, and CNF1.2 from top to bottom; (b) the sulfur loading is about 1 mg cm -2 Rate capacity data of carboxylated CNF cathode; (c) configured with 7 mg cm -2 Coin cell with sulfur-supported carboxylated CNF cathode; (d) 11 mg cm -2 Sulfur-supported carboxylated CNF cathode and 14 mg cm-2 as shown in the inset. -2 Sulfur loaded carboxylated CNF cathode; (e) Discharge areal capacity comparison among carboxylated CNF cathodes with different sulfur loadings; (f) Specific capacity and areal capacity of carboxylated CNF cathodes versus sulfur loading.
[0076] Figure 6 Pouch cell performance is shown; (a) long-term cycling of a pouch cell with a carboxylated CNF cathode; (b) Ah-level pouch cell with a carboxylated CNF cathode, with the pouch cell configuration shown in the inset; (c) discharge spectra of carboxylated CNF pouches and evolution of cycle life from the first cycle to the 40th cycle and the weight of each component used to calculate the specific energy shown in the inset table; (d) calculated specific energy relative to capacity of cathodes of Li-S pouch cells with different nominal voltages; (e) cycling spectra of two 2.5Ah pouch cells connected in series, with the inset photo showing the application of the package as a power battery for a drone; (f) battery cell performance comparison between the currently disclosed Ah-level carboxylated CNF pouch cell and the previously reported Ah-level Li-S pouch battery.
[0077] Figure 7 Shown are ex situ post-analysis SEM images of the lithium metal anode and sulfur cathode from a Li-S pouch cell after intensive cycling; (a) to (c) top-down SEM images of the lithium anode; (d) cross-sectional observations and (e) to (f) top-down SEM images of the carboxylated CNF cathode at a fully charged state.
[0078] Figure 8 Shown are transmission electron microscopy (TEM) images of (a) native CNFs and (b) carboxylated CNFs. DETAILED DESCRIPTION
[0079] It should be understood that the disclosure described and defined in this specification extends to all alternative combinations of two or more of the individual features mentioned or evident in the text or drawings. All these different combinations constitute various alternative aspects of the disclosure.
[0080] definition
[0081] For the purpose of interpreting this specification, terms used in the singular form will also include the plural form, and vice versa.
[0082] As used herein, the term "comprise" and variations of the term such as "comprising," "comprises," and "comprised" are not intended to exclude additional additives, components, integers or steps, unless the context requires otherwise.
[0083] As used herein, "about" when referring to a measurable value such as an amount, duration, etc., is intended to encompass variations of ±20% or ±10%, in some instances ±5%, in some instances ±1%, and in some instances ±0.1% relative to the specified value, as such variations are suitable for performing the disclosed methods.
[0084] Range: Throughout this disclosure, various aspects of the invention may be presented in a range format. It should be understood that description in a range format is merely for convenience and brevity, and should not be construed as a rigid limitation on the scope of the invention. Therefore, the description of a range should be considered to have all possible subranges specifically disclosed as well as individual numerical values within the range. For example, a description of a range such as 1 to 6 should be considered to have specific disclosed subranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 6, 3 to 6, etc., as well as individual numbers within the range, such as 1, 2, 2, 7, 3, 4, 5, 5.3, and 6. This applies regardless of the width of the range.
[0085] The present disclosure relates to a novel sulfur cathode for lithium-sulfur batteries. The cathode contains anion-functionalized cellulose nanofibers having a high surface charge. Lithium-sulfur batteries incorporating the novel sulfur cathode have many advantageous properties.
[0086] Sulfur cathode
[0087] A sulfur cathode according to the present disclosure comprises a mixture of a cellulose composition comprising a plurality of anion-functionalized cellulose nanofibers, one or more sulfur-containing materials, and one or more conductive materials.
[0088] In an embodiment, the presently disclosed sulfur cathode comprises:
[0089] a) about 2 wt.% to about 20 wt.% of a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers;
[0090] b) from about 60 wt.% to about 80 wt.% of one or more sulfur-containing materials; and
[0091] c) from about 10 wt. % to about 30 wt. % of one or more conductive materials.
[0092] In an embodiment, the presently disclosed sulfur cathode comprises:
[0093] a) about 5 wt.% to about 15 wt.% of a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers;
[0094] b) from about 65 wt.% to about 75 wt.% of one or more sulfur-containing materials; and
[0095] c) from about 15 wt. % to about 25 wt. % of one or more conductive materials.
[0096] In embodiments, the presently disclosed sulfur cathode comprises about 2 wt.% to about 20 wt.% of a cellulose composition, or about 3 wt.% to about 20 wt.%, or about 4 wt.% to about 20 wt.%, or about 5 wt.% to about 20 wt.%, or about 5 wt.% to about 19 wt.%, or about 5 wt.% to about 18 wt.%, or about 5 wt.% to about 17 wt.%, or about 5 wt.% to about 16 wt.%, or about 5 wt.% to about 15 wt.% of a cellulose composition.
[0097] The one or more sulfur-containing materials include one or more of elemental sulfur, Li2S, and MoS2. Other sulfur-containing materials typically used in sulfur cathode configurations are contemplated.
[0098] In embodiments, the presently disclosed sulfur cathode comprises about 60 wt.% to about 80 wt.% of one or more sulfur-containing materials, or about 61 wt.% to about 80 wt.%, or about 62 wt.% to about 80 wt.%, or about 63 wt.% to about 80 wt.%, or about 64 wt.% to about 80 wt.%, or about 65 wt.% to about 80 wt.%, or about 60 wt.% to about 79 wt.%, or about 60 wt.% to about 78 wt.%, or about 60 wt.% to about 77 wt.%, or about 60 wt.% to about 76 wt.%, or about 60 wt.% to about 75 wt.% of one or more sulfur-containing materials.
[0099] The one or more conductive materials include one or more of: carbon black, graphite, graphene, activated carbon, carbon nanotubes, and carbon fibers. Other conductive materials typically used in sulfur cathode constructions are contemplated.
[0100] In embodiments, the presently disclosed sulfur cathode comprises about 10 wt.% to about 30 wt.% of one or more conductive materials, or about 11 wt.% to about 30 wt.%, or about 12 wt.% to about 30 wt.%, or about 13 wt.% to about 30 wt.%, or about 14 wt.% to about 30 wt.%, or about 15 wt.% to about 30 wt.%, or about 15 wt.% to about 29 wt.%, or about 15 wt.% to about 28 wt.%, or about 15 wt.% to about 27 wt.%, or about 15 wt.% to about 26 wt.%, or about 15 wt.% to about 25 wt.% of one or more conductive materials.
[0101] Anion-functionalized cellulose nanofibers
[0102] Cellulose nanofibers are an integral component of delignified wood and are characterized by an aligned one-dimensional hierarchical structure rich in oxygen-containing polar functional groups (mainly hydroxyl groups) in the form of repeating anhydroglucose units constituting the cellulose molecular chain.
[0103] Cellulose nanofibers can be functionalized with a range of anionic functional groups. Examples of anionic functional groups include carboxyl, phosphonate, sulfonate, sulfate, hydroxyl, nitrate, and carbonate.
[0104] The functionality of the anionic functional groups can be expressed as mmol of anionic functional groups per gram of functionalized cellulose nanofibers. In an embodiment, the plurality of anion-functionalized cellulose nanofibers contain more than 1 mmol anionic groups per gram of nanofibers, or more than 1.25 mmol anionic groups per gram of nanofibers, or more than 1.5 mmol anionic groups, or more than 1.75 mmol anionic groups, or more than 2.0 mmol anionic groups, or more than 2.25 mmol anionic groups, or more than 2.75 mmol anionic groups, or more than 3.0 mmol anionic groups, or more than 3.25 anionic groups, or more than 3.5 mmol anionic groups.
[0105] In embodiments, the plurality of anionically functionalized cellulose nanofibers comprises about 1 mmol to about 4 mmol anionic groups per gram of nanofibers, or about 1.5 mmol to about 4 mmol anionic groups per gram of nanofibers, or about 2.0 mmol to about 4 mmol anionic groups or about 2.5 mmol to about 4 mmol anionic groups per gram of nanofibers.
[0106] In embodiments, the plurality of anionically functionalized cellulose nanofibers can be characterized by fibrils having favorable length, diameter, and aspect ratio, and high surface charge.
[0107] In embodiments, the plurality of anionically functionalized cellulose nanofibers have a fibril diameter of about 0.1 nm to about 20 nm, or about 0.5 nm to about 10 nm, or about 1 nm to about 6 nm, about 2 nm to about 4 nm.
[0108] In embodiments, the plurality of anionically functionalized cellulose nanofibers have a fibril length of about 20 nm to about 1000 nm, or about 40 nm to about 700 nm, or about 70 nm to about 500 nm, or about 100 nm to about 400 nm.
[0109] In embodiments, the plurality of anionically functionalized cellulose nanofibers has a fibril aspect ratio of about 10 to about 1000, or about 15 to about 750, or about 20 to about 500, or about 25 to about 200.
[0110] The anionically functionalized cellulose nanofibers according to the present disclosure can have a high surface charge. In embodiments, the zeta potential of the anionically functionalized cellulose nanofibers can be more negative than about -60 mV, or more negative than about -65 mV, or more negative than about -70 mV, or more negative than about -75 mV, or more negative than about -80 mV.
[0111] In embodiments, the zeta potential of the anionically functionalized cellulose nanofibers may be about -60 mV to about -90 mV, or about -60 mV to about -90 mV, or about -60 mV to about -80 mV, or about -70 mV to about -90 mV, or about -70 mV to about -80 mV.
[0112] Without wishing to be bound by theory, it is envisioned that the anionic groups of the functionalized cellulose nanofibers can facilitate the transport of Li ions when used as a component of a sulfur cathode due to the resulting negatively charged microenvironment, but enable electrostatic repulsion of polysulfides with anionic character.
[0113] Preparation of anion-functionalized cellulose nanofibers
[0114] Native cellulose nanofibers can be treated with appropriate reagents to introduce anionic functional groups into the cellulose molecular chains. Many methods for introducing such functional groups are known in the art.
[0115] For example, methods that can be used to introduce carboxyl functional groups are described in Mendoza, DJ, Browne, C., Raghuwanshi, VS, Simon, GP, and Garnier, G. One-shot TEMPO-periodate oxidation of native cellulose. Carbohydrate polymers 226, 115292 (2019).
[0116] After anionic functionalization of the cellulose nanofibers, they may be subjected to high shear conditions to reduce one or more fibril sizes. Suitable high shear conditions include, for example, one or more of high pressure homogenization, ultrasonic homogenization, grinding, and cryogenic ball milling.
[0117] Sulfur cathode characteristics
[0118] A characteristic of the presently disclosed sulfur cathode is its relatively low porosity. This is advantageous because it minimizes the cathode pore volume and, therefore, the electrolyte volume.
[0119] The porosity of the sulfur cathode may be less than about 50%, or less than about 45%, or less than about 40%, or less than about 35%.
[0120] Another feature of the currently disclosed sulfur cathode is its relatively low surface roughness. In an embodiment, the cathode has an arithmetic surface roughness of less than about 25 μm, or less than about 20 μm, or less than about 15 μm, or less than about 10 μm. In an embodiment, the arithmetic surface roughness may be from about 5 μm to about 25 μm, or from about 5 μm to about 20 μm, or from about 5 μm to about 15 μm.
[0121] Without being bound by theory, the observed low surface roughness can be attributed to the self-relaxation and orientation ability of the semi-crystalline anion-functionalized cellulose nanofibers. The sulfur cathode can contain fewer agglomerated particles due to the repulsive forces generated by the high apparent surface charge of the cellulose nanofibers. Considering the cathode of a lithium metal battery system, each tip of the rough surface has a high electric field, which attracts more Li ion flux and promotes the formation of dendrites. From this perspective, a useful cathode should have the desired characteristics of a relatively smooth surface, especially for large-scale applications, to minimize the duplication and amplification of surface defects.
[0122] Preparation of sulfur cathode
[0123] The presently disclosed sulfur cathodes can be prepared by first combining a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers with one or more sulfur-containing materials, one or more conductive materials, and water to form a cathode slurry.
[0124] In some embodiments, the solid components are dry mixed prior to combining with water.
[0125] An advantageous property of the cathode slurry disclosed herein is its viscosity. In the examples, the viscosity of 3 ml water / g total solid slurry is 0.01 s when measured in the temperature range of 20-25°C. -1 The viscosity at the shear rate is greater than about 1000 Pa.s.
[0126] In the examples, when measured in the temperature range of 20-25°C, 3 ml / g of the slurry has a -1 The viscosity at the shear rate is about 1000 Pa.s to about 3000 Pa.s.
[0127] Useful cathode slurries may be prepared at a ratio of about 3 ml / g to about 30 ml / g of water to total solids.
[0128] The sulfur cathode can be prepared by coating the cathode slurry on an aluminum foil and drying. Optionally, the coated foil can be subjected to calendering.
[0129] Lithium-sulfur battery
[0130] The present disclosure provides a lithium-sulfur battery, which comprises a lithium anode, a separator, a cathode according to any one of the embodiments disclosed herein, and an electrolyte disposed between the anode and the cathode.
[0131] In an embodiment, the ratio of electrolyte volume to sulfur weight in the lithium-sulfur battery is less than about 6.0 μl / mg.
[0132] In embodiments, the ratio of electrolyte volume to sulfur weight in the lithium-sulfur battery is less than about 6.0 μl / mg, or less than about 5.5 μl / mg, or less than about 5.0 μl / mg, or less than about 4.5 μl / mg, or less than about 4.0 μl / mg, or less than about 3.5 μl / mg.
[0133] In an embodiment, the ratio of electrolyte volume to sulfur weight in the lithium-sulfur battery is about 3.5 μl / mg to about 5.0 μl / mg.
[0134] Typical separators known in the field of lithium-sulfur batteries may be used.
[0135] The sulfur loading was 16.6 mg cm-1 with a slurry containing 70 wt.% sulfur, 20 wt.% carbon, and 10 wt.% carboxylated cellulose nanofibers (about 2 mmol carboxyl groups per gram of nanofibers). -2 The cathode prepared in the button cell provides up to 25 mAh cm -2 The areal capacity of 1500mAh g is equivalent to 1500mAh g, while achieving a coulombic efficiency of >98%. -1 specific capacity and 89% sulfur utilization.
[0136] Ah-scale Li-S pouch cells prepared with similar cathode compositions provided over 1200 mAh g -1 The initial capacity and approximately 15 mAh cm -2 area capacity, resulting in up to 330Wh kg -1 High gravimetric energy and 367Wh L -1 volume energy density.
[0137] Examples
[0138] Material
[0139] Elemental sulfur was purchased from Sigma-Aldrich. Conductive carbon powder was purchased from Shandong Gelon LIB Co., LTD, China for Cabot Corporation (CABOT) blackpearl2000. Cellulose nanofibers (CNF) were provided by the University of Maine (The University of Maine, USA) or BioPRIA Institute (BioPRIA, Monash University, Australia) of Monash University, Australia. Carbon-coated glass fiber interlayers include carbon (ASAC30, Canadian Adven Industries Inc. (AdvenIndustries Inc., Canada)), gum arabic (HawkinsWatts) and glass fiber (BG03013 diaphragm, Hollingsworth & Vose, USA (Hollingsworth & Vose, USA)). Bis(trifluoromethane)sulfonyl imide lithium salt and lithium nitrate were purchased from Sigma-Aldrich and used directly without any further purification. 1,2-Dimethoxyethane (DME) and dioxolane (DOL) solvents were purchased from Sigma-Aldrich. Li2S was purchased from Alfa Aesar for lithium polysulfide synthesis. Battery-grade aluminum foil was purchased from Japan Capacitor Industrial Co., Ltd., and battery-grade copper foil was purchased from Shandong Gelon LIB Co., LTD, China. Celgard 2730 separator was purchased from Celgard Inc., USA. CNT was purchased from NanoFibers, UK. Lithium chips (16*0.2mm) were purchased from Shandong Gelon LIB Co., LTD, China.
[0140] Preparation of carboxylated cellulose nanofibers
[0141] Carboxylated cellulose nanofibers were synthesized by one-step 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO)-periodate oxidation of bleached eucalyptus kraft pulp (BEK) of native cellulose nanofibers (CNF) as described in Mendoza, DJ, Browne, C., Raghuwanshi, VS, Simon, GP and Garnier, G. One-step TEMPO-periodate oxidation of native cellulose Carbohydrate Polymers 226, 115292 (2019). High pressure or ultrasonic homogenization of the resulting oxidized BEK fibers resulted in the formation of highly charged cellulose nanofibers. In one example, a suspension of oxidized fibers (0.01 wt%) was sonicated for 2 minutes using an ultrasonic homogenizer at 19.5 kHz and 70% amplitude (on / off, 5 seconds).
[0142] Aqueous virgin cellulose nanofiber dispersions were imaged by polarized light microscopy using an LC-PolScope microscope. Figure 1 As shown in a, high birefringence regions were observed with aligned domain lengths of about 100-200 μm and widths of about 20-50 μm. In contrast, the size of the carboxylated CNFs ( Figure 1 b; aligned domain length of about 30-50 μm and width of about 10-20 μm) is significantly smaller than the size of native CNFs.
[0143] Effect of surface charge and aspect ratio on cellulose nanofibers
[0144] A series of carboxylated CNFs with various carboxylic acid group contents were studied. In general, as more carboxylic acid groups were introduced, the fibers broke down, increasing the surface charge and decreasing the aspect ratio.
[0145] Samples labeled CNF2, CNF1.5, CNF1.4, and CNF1.2 were prepared to nominally contain 2 mmol, 1.5 mmol, 1.4 mmol, and 1.2 mmol carboxyl groups per gram of solid.
[0146] Figure 2 a shows the relationship between the carboxylic acid content of CNF samples and the corresponding surface charge as measured by zeta potential. Levels of carboxylic acid content between about 1.3 mmol / g and 1.9 mmol / g were examined. High levels of carboxylic acid groups resulted in significant surface charges up to -80 mV.
[0147] In addition, lithium polysulfide adsorption tests provide evidence of polysulfide confinement within highly charged carboxylated solids. Cellulose binders are commonly used in electrode fabrication and have relatively low surface charges (-20 mV to 30 mV; see Figure 2 a) showed less polysulfide adsorption than carboxymethyl cellulose (CMC).
[0148] Carboxylated CNFs with different surface charges were solid dispersed in water and subjected to rheological testing. Figure 2 Steady-state shear rheology depicted in b shows that all carboxylated CNF samples have similar degrees of shear thinning properties. However, the zero shear viscosity of the carboxylated CNF samples was observed to increase steadily with surface charge. This may be due to the higher level of fibril formation promoted by repulsion between negatively charged carboxylated CNFs, resulting in high nanofiber content and strong network structure.
[0149] The electrolyte wettability of carboxylated CNF films is represented by the contact angle between the film and the electrolyte droplet, as Figure 2 c. The contact angle of the sample decreases within 10 seconds after a drop of electrolyte falls on the surface of the carboxylated CNF film. Figure 2 In the graph in c, it can be clearly observed that the increase in surface charge leads to a decrease in the contact angle. This may be because the increase in the concentration of carboxylic acid groups weakens the hydrogen bonds between the hydroxyl groups in the carboxylated CNF film and helps the ester solvent present in the electrolyte to be absorbed faster.
[0150] To make a relative comparison of the ionic conductivity of the carboxylated CNF samples, a membrane immersed in a 0.5 wt.% carboxylated CNF solution was used in a symmetric battery cell. Figure 2 As depicted in (d), it can be seen that the increase in surface charge leads to an increase in ionic conductivity, indicating that the carboxylic acid groups are more conducive to ion transfer than the hydroxyl groups.
[0151] Preparation of sulfur cathode
[0152] The cathode slurry was prepared by dry mixing all the components in the following order using a magnetic stirring bar (600 rpm, room temperature and dry environment). Sulfur (0.7 g) and conductive carbon powder (0.2 g) were mixed for 24 hours, followed by adding different carboxylated CNF powders (0.1 g) to the mixture, and continuing to dry mix all three components for another 24 hours. Then, 3 mL of deionized (DI) water was added to 1 g of the well-mixed components. All components were mixed in water with a magnetic stirring bar (600 rpm, room temperature and air environment) for 12 hours to produce a homogeneous slurry. All sulfur cathode slurries were coated on battery-grade Al foil by a laboratory-grade doctor blade and dried at room temperature for 6 hours, followed by drying under vacuum at 80 ° C for 12 hours to remove all traces of the solvent. The cathode was not calendered before the button cell and pouch cell assembly.
[0153] The cathode slurry was prepared by mixing 10 wt.% carboxylated CNF, 70 wt.% sulfur particles and 20 wt.% carbon particles. The structure of the cathode slurry was also observed by polarized light microscopy. Figure 1 As shown in c, when native CNFs are used, there is no trace of any birefringent structure.
[0154] In contrast, carboxylated CNFs are characterized by high surface charge and low aspect ratio. At the same solid content, slurries with carboxylated CNFs contain a higher number density of fine fibers that can form domains. Figure 1 As depicted in (d), the carboxylated CNF slurry forms liquid crystalline domains, which are evident from the high retardation patches exceeding the size of individual fibers. These long-range ordered structures suggest that stacked structures can form in 3D films.
[0155] Additional testing showed that this self-organizing ability of the slurry is concentration dependent and may be driven by the osmotic pressure enhancement caused by the increase in counter-ion charge. In the low concentration slurry (3.3 mg / ml), it was noted that the carboxylated CNFs showed optical retardation dispersed in the isotropic medium. The isotropic medium is a carbon slurry without any optical retardation ( Figure 1 e). At a higher concentration of 33.3 mg / ml ( Figure 1 f), the proportion of crystallized carboxylated CNF increased in the slurry, as is evident from the images. Finally, the slurry of 333.3 mg / ml ( Figure 1 g) shows high-retardation patches. As the fraction of nanofibers in the dispersion increases, the fibers become orderedly driven by the reduced orientation entropy. The loss of this orientation entropy is compensated by increasing the translational entropy, thereby releasing more space for new fibers, because the new fibers are aligned in orientation. These results show that even in the case of sulfur and carbon particles present in the free volume in the carboxylated CNF domain, the cathode can still form an ordered structure driven by osmotic pressure during drying.
[0156] Morphology and conductivity of cathodes containing cellulose nanofibers
[0157] A profilometer was used to check the cathode morphology. Figure 3 a), the surface is not uniform and, according to the roughness spectrum, its height difference is about 276 μm. Scanning electron microscopy (SEM) images support this observation. Pits can be clearly identified on the surface of the cathode made of CMC ( Figure 3 b) Study the microstructure of the cathode under high magnification SEM, such as Figure 3c, and the image depicts severe aggregation of particles. In contrast, the cathode prepared with carboxylated CNF (CNF2) showed relatively low surface roughness, with a height difference of about 165 μm ( Figure 3 d). SEM images of carboxylated CNF cathodes provide additional evidence of their smooth surface ( Figure 3 e) In addition, Figure 3 The uniformly distributed particles of the carboxylated CNF cathode are clearly observed in f.
[0158] The texture of carboxylated CNF is depicted in detail under high magnification top view SEM ( Figure 3 gi). Figure 3 g shows the interlocking and mechanically robust microstructure of carboxylated CNFs in the sulfur cathode. Another region of carboxylated CNFs is shown in Figure 3 h, and in Figure 3 i. This region of the carboxylated CNF exhibits a highly porous structure. Figure 3 As shown in Figure 5, the carboxylated CNFs act as the cathode skeleton and support the three-dimensional structure through the entire cross section of the cathode. The cross-sectional SEM image is shown in Figure 5. Figure 3 km, the stacked and separated structures are consistent throughout the carboxylated CNF cathode. This feature may be beneficial for ion transport due to the excellent electrolyte retention properties and shortened ion transport pathways. In addition, these mesopores accommodate the volume expansion of sulfur particles during charge and discharge to maintain the integrity of the cathode.
[0159] The porosity of the lithium-sulfur cathode can be estimated based on thickness measurements obtained from SEM cross sections and the following equation:
[0160]
[0161] where V(cathode) is the geometric volume of the electrode calculated using the thickness of the cathode, and V 致密 (cathode) is the dense volume of the cathode calculated by taking the measured mass of the coating and dividing it by the average density of all cathode components as determined by a gas pycnometer.
[0162] The calculated figure for the cathode is 33.6% porosity, which is significantly lower than the porosity of previously reported sulfur cathodes. The highly negatively charged carboxylated CNFs have a significant impact on the cathode architecture. They help retain the porous structure but also compress the cathode with repulsive forces. Positron annihilation lifetime spectroscopy (PALS) tests show the relationship between CNF surface charge and pore size. As the surface charge increases, the pore size decreases from 0.428nm (CNF1.2) to 0.411nm (CNF2). The synergistic effect of uniformly distributed pores and relatively high compactness of the cathode is beneficial for volumetric energy density evaluation.
[0163] Examining the electrical and ionic conductivity of CNF thick cathodes
[0164] Electron beam absorption current (EBAC) measurements were performed to evaluate the equivalent of 14 mg cm -2 Electrical properties of sulfur-loaded CMC and carboxylated CNF thick cathodes. Figure 4 As shown in a, a movable current source is provided by a scanning electron beam in the SEM. An external circuit measures the local absorption current flowing between the electron probe incident position and the cathode substrate. The absorption current spectrum perpendicular to the cathode thickness direction of each cathode is captured by an EBAC amplifier ( Figure 4 e and Figure 4 f), and Figure 4 The spectrum is drawn in b. It can be clearly seen in this figure that the average EBAC current from the carboxylated CNF cathode is greater than the current from the CMC cathode. Although the EBAC measurement is sensitive to sample surface roughness and porosity due to the change of secondary electron emission and backscattered electron emission, it can be used as an indicative technique for measuring electrical conductivity, as long as the two samples have the same composition and similar porosity. In addition, the current is averaged perpendicular to the spectral analysis direction in each box to minimize the influence of surface roughness in different samples. By measuring the resistance between the top of the cathode and between the cathodes, the in-plane conductivity of the CMC cathode and the carboxylated CNF cathode was also tested. The resistance of the CMC cathode and the carboxylated CNF cathode is 61.1 ohms and 34.5 ohms respectively, which shows that the electrical conductivity (electrical / electronic conductivity) of the carboxylated CNF cathode is better than that of the CMC cathode.
[0165] It is also noted that the EBAC current spectrum at the carboxylated CNF cathode (standard deviation 5.48 × 10 -11 ) in the CMC cathode (standard deviation 6.48×10 -11 ) fluctuates within a smaller range than that in the CMC cathode, indicating that the conductivity of the carboxylated CNF cathode is more uniform despite its greater thickness. Figure 4 c and 4d) and in situ EBAC mapping ( Figure 4 e and 4f) for further details. It is worth noting that in Figure 4 In Figure c, there is an obvious phase separation between the top and bottom parts of the CMC cathode. Due to this phase separation, Figure 4e shows that the EBAC current on the bottom part is much lower. Based on the EDX line scan spectrum and corresponding elemental mapping on the cross section of the CMC cathode, the concentration of sulfur element is higher and the concentration of carbon element is lower in the bottom region. This is attributed to the larger particle size and higher density of crystalline sulfur, which will settle on the bottom of the cathode due to the low viscoelastic slurry and unstable cathode structure during the coating and drying process. In contrast, there is no obvious phase separation in the carboxylated CNF cathode ( Figure 4 d and 4f), which indicates that the carboxylated CNF cathode slurry has good rheological properties and provides evidence of a more homogeneous distribution of sulfur particles and conductive agent (carbon).
[0166] The ionic conductivity was examined using cyclic voltammetry (CV). The calculations were performed using a series of cyclic voltammograms with different scan rates according to the Randles-Sevick equation. For the CMC cathode, the value of the lithium ion diffusion coefficient was 1.05 × 10 - 6 cm 2 s -1 to 2.92×10 -7 cm 2 s -1 , and for the carboxylated CNF cathode, the value is 3.25×10 -6 cm 2 s -1 to 1.21×10 -6 cm 2 s -1 The increased lithium ion diffusion coefficient of the carboxylated CNF cathode confirms the enhanced lithiation / delithiation kinetics and ionic conductivity of the sulfur cathode with carboxylated CNF system.
[0167] Coin Cell Assembly and Electrochemical Testing
[0168] A glass fiber interlayer (0.203 mm thickness, 16 mm diameter, and 15.5 μm maximum pore size) was coated with an aqueous slurry mixture of 80 wt.% carbon and 20 wt.% gum arabic (8 mL of deionized (DI) water was added to 1 g of the uniformly mixed components) as the conductive layer on the sulfur cathode. In order to match the sulfur cathode with different sulfur loadings, the carbon content of the aforementioned carbon-coated glass fiber interlayer was 200 wt.% and 100 wt.% for sulfur loading of 3 mg cm -2 The sulfur cathode is 1 mg cm -2 , for a sulfur loading of 6 mg cm -2 The sulfur cathode is 1.5 mg cm -2 , and for a sulfur loading of 11 mg cm -2 The sulfur cathode is 2 mg cm -2. Therefore, the total sulfur content including the sulfur cathode and the conductive interlayer was 56.7%-62.1%. A Celgard membrane (Celgard 2730, 20 μm thickness, 16 mm diameter, 1 μm pore size and 43% porosity) was used as a separator. The electrolyte (<0.003% water content) was prepared by dissolving 1 M lithium bis(trifluoromethane)sulfonamide (LiTFSI) and 0.5 M lithium nitrate (LiNO3) in DOL and DME (1:1, v / v) in an argon-containing glove box (<0.1 ppm H2O and <0.1 ppm O2). The electrolyte to sulfur ratio was 8.6-22 μL mg -1 This is in the range of 2.5 to 3.0, depending on the sulfur loading. For example, for 3 mg cm -2 15 μL of electrolyte was used to wet the cathode. To wet the carbon-coated glass fiber and Celgard separator, 50 μL of electrolyte was used. For 6 mg cm -2 20 μL of electrolyte was used to wet the cathode. To wet the carbon-coated glass fiber and Celgard separator, 60 μL of electrolyte was used. For 11 mg cm -2 For the cathode, 25 μL of electrolyte was used to wet the cathode. To wet the carbon-coated glass fiber and Celgard separator, 70 μL of electrolyte was used. In general, increasing amounts of electrolyte were used to increase the sulfur loading of the cathode. Greater than 20 μL mg -1 The E / S ratio is defined as the condition of electrolyte overflow and is lower than 5 μL mg -1 An E / S ratio of 1.0 is defined as an electrolyte-depleted condition.
[0169] For the coin cell assembly, all steps were performed in an argon glove box, and electrochemical testing was performed by EC-lab (Bio-logic) under air atmosphere and room temperature. The results were obtained in the frequency range of 1 mHz to 1 MHz, 6 data points per decade, 10 mV rms alternating current (AC) voltage and relative to E 参考 EIS measurements were performed with a potentiostatic signal at 2.8 V direct current (DC).
[0170] Coin cell testing and electrochemical characterization of CNF cathodes
[0171] To verify the effect of different carboxylated CNF cathodes on the cycling performance, coin cell cells were configured with cathodes containing sulfur, carbon, and carboxylated CNF with different surface charges. The coin cell cells were cycled at 0.5C rate (0.5C) for 200 cycles. Figure 5As shown in Figure 1, the results show that all carboxylated CNF cathodes can establish relatively stable cycle life at high charge and discharge rates, while the capacity and capacity retention increase with the enhancement of CNF surface charge. Figure 5 As shown in (b), the cathode composed of carboxylated CNFs with higher surface charge was demonstrated to improve the rate capacity from 0.1 C to 1 C. These results can be explained by the better electrolyte wettability and more efficient Li ion transport of carboxylated CNFs with higher surface and lower aspect ratio.
[0172] Given the enhanced electrical and ionic conductivity of the self-supporting structure and the carboxylated CNF thick cathode, coin cell performance tests were performed using cathodes with high sulfur loading. The sulfur loading was 7 mg cm -2 The cathodes based on CNF2 and CNF1.2 were cycled at 0.1C. Comparison of the results ( Figure 5 c) shows that the stability of the CNF2-based cathode is improved and the specific capacity is higher. In addition, the sulfur loading is 11 mg cm -2 and 14 mg cm -2 The CNF2-based cathode ( Figure 5 d) also maintains a high reversible capacity with a Coulombic efficiency of about 98%. The cathode was further explored for 16.6 mg cm -2 The sulfur loading tolerance is shown in Figure 5 e. The areal capacity of CNF2-based cathode is as high as 25 mAh cm -2 , with good stability retention rate. Figure 5 f) shows the relationship between specific capacity and areal capacity versus sulfur loading. It is noteworthy that the specific capacity of the CNF2-based cathode no longer decreases with increasing sulfur loading. The capacity of the thick CNF2-based cathode at 1200 mg cm -2 With 1500mgcm -2 The floating specific capacity is a sulfur loading-independent parameter, which is different from the prior art lithium-sulfur batteries. The battery's areal capacity continues to increase with increasing sulfur loading, which means that thick cathodes do not hinder the utilization of active materials.
[0173] Pouch cell preparation
[0174] About 4 mg cm -2 The sulfur cathode was cut into 3 cm × 5 cm (cathode and Al substrate). About 6.5 mg cm -2The sulfur cathode is cut into 6cm×5cm (cathode and Al substrate). For double-sided cathodes, sulfur slurry is coated on the back of the single-sided cathode to produce some sulfur loading on both sides. Li foil (0.1mm or 0.05mm thickness) is cut to the same size as the sulfur cathode (3cm×5cm). The Al gasket is welded to the prepared cathode, and the Ni gasket is adhered to the Li anode by a conductive Cu cage / double spot welder. Subsequently, a carbon-coated glass fiber interlayer or a carbon nanotube (CNT) paper interlayer is stacked on the Celgard separator, followed by stacking the cathode on top of the interlayer. Then, a Li anode is placed on the other side of the Celgard separator. An electrolyte between 3.5μL and 5μL is injected into the stack, and the package is sealed under vacuum. All battery cells are assembled in an Ar-containing glove box (<0.1ppm H2O and <0.1ppm O2).
[0175] Verification of Ah-level Li-S pouch cells
[0176] Considering the excellent coin cell performance of CNF2-based cathodes, pouch cells were assembled with 450 mg sulfur loading in double-sided cathodes with dimensions of 3 cm × 4.5 cm. The 450 mg pouch cells were cycled at 0.05 C. The cells showed over 900 mAh g -1 The specific capacity of the battery is 70% after 100 cycles, and the Coulombic efficiency is >95%. Figure 6 a).
[0177] Also like Figure 6 As shown in the insert in b, Ah-scale CNF2-based cathode pouch cells were fabricated to validate the prototype with high sulfur loading, thin Li anode, and electrolyte-poor operation. Parameters include 12 mg cm -2 Sulfur-loaded double-sided cathode, 1.35 negative electrode to positive electrode capacity ratio (N / P ratio) and 5 μl mg -1 Electrolyte to sulfur ratio (E / S ratio). Figure 6 As shown in b, the Ah-class pouch cell is subjected to 0.05C (equivalent to 82mA g -1 The specific capacity at the current density is about 1200 mAh g -1 , indicating high sulfur utilization even at high sulfur loading and high current density. As a result, the battery cell delivers 330Wh kg -1 The actual specific energy of each component used in the calculation is given in the table Figure 5 c to insert the card into the table. Figure 6 From the discharge diagram depicted in c, the Ah-level bag establishes a standard discharge spectrum and maintains the second plateau of 2.1 V from the first cycle to the 40th cycle.
[0178] The specific energy of the pouch cell was calculated based on the following equation:
[0179]
[0180] E g : Specific energy (Wh kg -1 )
[0181] V: Output voltage (V)
[0182] C: Output capacity (mAh)
[0183] ∑m i : Total weight (including cathode, anode, conductive interlayer, separator, electrolyte)
[0184] like Figure 6 As shown in c, at the same specific capacity and total weight, the specific energy is significantly reduced at low nominal voltage. For example, the calculated specific energy is only 260 Wh kg at a nominal voltage of 1.8 V. -1 , but at 2.1V nominal voltage it is 300Whkg -1 The nominal voltage is dominated by the reaction kinetics in the battery, which requires good ionic conductivity and electrical conductivity in the battery cell. Current Ah-class bags can achieve high voltages even under poor electrolyte conditions (5 μl mg -1 ) and thick sulfur-loaded cathodes (12 mg cm -1 ), which can be attributed to the optimized structure of the CNF2-based cathode. The dimensions of the bag were measured, and the volumetric energy density was calculated to be 367Wh L -1 .
[0185] The performance of current pouch cell batteries was further examined by powering drones, which requires high gravimetric energy density and high power (current density). Figure 6 The graph in e shows the cycling profile of two 2.5Ah bags connected in series to provide the operating voltage of the drone. Flight tests of the drone showed that the Li-S bag was able to support 10 minutes of hovering time before reaching the cut-off voltage. Capacity testing of the bag after service showed that only one-third of the capacity was consumed during the 10-minute flight test, which means that the hovering time can potentially be tripled with an optimized voltage regulator and control board design.
[0186] like Figure 6 As shown in Figure 5, the cathode pouch cell based on CNF2 combines high specific energy, long cycle life and high specific capacity. It is worth noting that 15 mAh cm -2The currently disclosed pouch cell outperforms other reported Ah-class Li-S pouch cell.
[0187] Summary of key features and compared systems
[0188] Sulfur cathodes prepared by mixing 70 wt.% sulfur, 20 wt.% carbon, and 10 wt.% of different binder systems in deionized (DI) water were compared, and the results are collected in the table. Systems 1 and 2 used carboxymethyl cellulose (CMC), a commonly used binder in battery electrode manufacturing, in both wet mixing (system 1) and dry mixing (system 2). Previous publications have shown that CMC enables the formation of strong bridging bonds between sulfur and carbon particles by dry mixing of solid components before adding water (see International Patent Application No. PCT / AU2019 / 051239). System 3 uses a CMC glucose binder as disclosed in Y. Huang et al., Nature Communications, (2021), 12: 5375. System 4 is in accordance with the present disclosure and utilizes carboxylated CNF with about 2 mmol / g carboxyl loading (CNF2).
[0189]
[0190] From the results, system 4 according to the present disclosure has a desirable range of characteristics including cathode slurry viscosity, ease of processing, very low cathode porosity, high areal capacity at high sulfur loading, and low electrolyte to sulfur volume to weight ratio.
[0191] Ex situ post-mortem analysis of Li-S pouch battery cells
[0192] After intensive cycling, the pouch cells were disassembled and the lithium metal anode and sulfur cathode were washed by DOL / DME and collected for SEM imaging. Figure 7 As shown in a, the surface of the lithium anode has two different morphologies. The first morphology ( Figure 7 b) is a thick solid electrolyte interphase (SEI) layer film for lithium plating covering the emerging stone-shaped morphology. Another part of the lithium surface ( Figure 7 c) are filled with mature stone shapes with low surface area, rather than the detrimental dendrite growth often observed in previously reported systems. This desirable lithium plating behavior maintains the integrity of the SEI layer, which can be attributed to the controlled ingress of lithium polysulfides into the lithium anode. This regulated ability of the system is the synergistic effect of the highly negatively charged CNFs in the cathode, which hinder the migration of negatively charged polysulfides from the cathode and the carbon-coated thin glass fiber interlayer, thereby limiting the transport of lithium polysulfides.
[0193] For example, the cross section of a CNF-based cathode in a fully delithiated state ( Figure 7 d) and overlooking ( Figure 7 e) SEM, the cathode does not show severe cracks after cycling, thanks to the separated microstructure that accommodates volume changes during cycling. Higher magnification images provide more structural details ( Figure 7 e) The CNF-based cathode shows that the bonding between particles is preserved, indicating the high robustness of the carboxylated CNF framework.
[0194] Microscopy analysis of cellulose nanofibers
[0195] Diluted suspensions of pristine CNFs and carboxylated CNFs in water (about 0.001 wt %) were sonicated with an ultrasonic probe at 70% amplitude for 2 min and analyzed by transmission electron microscopy. Figure 8 An image is shown.
[0196] The samples were broken down into nanofibers with a measured fibril diameter of less than 4 nm. Figure 8 (a)) showed long and aggregated nanofibers (fibril length was about 1000 nm), while the carboxylated CNF sample ( Figure 8 (b) ) Shows shorter individual nanofibers with improved separation (fibril length 500 nm).
[0197] Analytical techniques
[0198] Scanning electron microscopy imaging and EDX mapping
[0199] Freshly prepared cathode samples were mounted on aluminum stakes with conductive carbon taps and coated with iridium for front and cross-sectional imaging. Secondary electron imaging and energy dispersive chromatography mapping (EDX) were performed using a Nova 450 field emission scanning electron microscope (FESEM) and a Magellan 400 FESEM. For ex situ post-analysis SEM studies, all battery cells were terminated at full charge and then disassembled in an argon glove box. The cycled electrodes (cathode and anode) were washed with 1 ml DOL / DME (1:1, v / v) and vacuum dried for 12 hours before being mounted on aluminum stakes with conductive carbon taps in an argon glove box. A transfer vacuum module was used to transfer the cycled electrodes from the argon glove box to the Merlin FESEM for analysis.
[0200] Transmission electron microscopy imaging
[0201] Transmission electron microscopy (TEM) was performed using a FEI Tecnai F20. Diluted suspensions of native CNF and carboxylated CNF (about 0.001%) were sonicated with an ultrasonic probe at 70% amplitude for 2 minutes and allowed to dry on a plasma-cleaned copper grid. The samples were then stained with 2% uranyl acetate, air dried, and examined at 200 kV.
[0202] Rheological measurements
[0203] Rheological measurements were performed using a strain-controlled ARES G2 rheometer (TA instruments, USA) using cone-plate geometry (diameter - 50 mm, cone angle - 2°). A constant gap of 0.045 mm and a temperature of 23.00 ± 0.01 °C were maintained during the measurement. For steady-state measurements, the flow rate was recorded as the flow rate increased with the increase in the flow rate at 0.1 s. -1 Up to 100s -1 The viscosity change was determined by varying the shear rate over a range of 100 rad / s. Amplitude sweeps were performed over a strain amplitude range of 0.1% to 100% at an angular frequency of 10 rad / s to determine the linear viscoelastic (LVE) behavior. Frequency sweeps were performed over a range of 0.1 rad / s to 100 rad / s.
[0204] Electron Beam Absorption Current (EBAC) Measurement
[0205] EBAC measurements were performed in a FEI (FEI) Nova NanoSEM450FEG SEM equipped with a DEBEN (DEBEN) GW 31 amplifier. The battery electrode cross-section sample was mounted on a thin glass slide to provide electrical isolation from the SEM level. Then, it was connected to the cross-section sample pile along the side-standing orientation relative to the electron beam. Through a vacuum feedthrough, the electrode copper substrate was connected to the EBIC amplifier, which converts the current signal into a voltage output in the range of 0-1V and is then digitized to a 16-bit grayscale value by the SEM system. All EBAC drawings were obtained using an electron beam of 5kV, a spot size of 5, and a 50μm objective aperture, resulting in an incident beam current of about 5nA. Due to the limited amplifier bandwidth in quantitative mode, the scan dwell time was set to a conservative 8.2 milliseconds. For each drawing, the dark current was obtained by blanking the electron beam in the first few rows of the scan and then deducting it in post-processing.
[0206] Surface roughness measurement
[0207] The profilometry measurements of the electrodes were performed using an Olympus LEXT OLS5000 laser confocal microscope. Each scan took about 5 minutes. The instrument automatically calculated the arithmetic surface roughness R a .
[0208] Zeta potential
[0209] Carboxylated and homogenized CNF were subjected to centrifugation at 12,000 g for 5 minutes to separate any unfibrillated fibers. The resulting supernatant was analyzed by dynamic light scattering and zeta potential analysis using a particle size and zeta potential analyzer (Brookhaven Nanobrook Omni). Five measurements were performed for each sample.
Claims
1. A sulfur cathode comprising: a) a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers; b) one or more sulfur-containing materials; and c) One or more conductive materials.
2. The sulfur cathode according to claim 1, comprising: a) 2-20 wt.% of a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers; b) 60-80 wt.% of one or more sulfur-containing materials; and c) 10-30 wt. % of one or more conductive materials.
3. The sulfur cathode according to claim 1, comprising: a) 5-15 wt.% of a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers; b) 65-75 wt.% of one or more sulfur-containing materials; and c) 15-25 wt. % of one or more conductive materials.
4. The sulfur cathode according to any one of claims 1 to 3, wherein the plurality of anion-functionalized cellulose nanofibers have one or more of the following properties: a) a fibril diameter of about 0.1 nm to about 20 nm; b) a fibril length of about 20 nm to about 1000 nm; c) a fibril aspect ratio of about 10 to about 1000; and d) The zeta potential is more negative than about -60 mV.
5. The sulfur cathode of any one of claims 1 to 4, wherein the one or more sulfur-containing materials comprise one or more of elemental sulfur, Li2S, and MoS2.
6. The sulfur cathode of any one of claims 1 to 5, wherein the one or more conductive materials comprise one or more of the following: carbon black, graphite, graphene, activated carbon, carbon nanotubes, and carbon fibers.
7. The sulfur cathode of any one of claims 1 to 6, wherein the cathode has a porosity of less than 50% or less than 40%.
8. The sulfur cathode according to any one of claims 1 to 7, wherein the cathode has an arithmetic surface roughness of less than 25 μm.
9. The sulfur cathode of any one of claims 1 to 8, wherein transport of polysulfide anions within the cathode is hindered relative to a sulfur cathode in the absence of the cellulose composition.
10. The sulfur cathode of any one of claims 1 to 9, wherein transport of lithium ions within the cathode is facilitated relative to a sulfur cathode in the absence of the cellulose composition.
11. A lithium-sulfur battery comprising a lithium anode, a separator, a cathode according to any one of claims 1 to 10, and an electrolyte disposed between the anode and the cathode.
12. The lithium-sulfur battery of claim 11, wherein the ratio of electrolyte volume to sulfur weight is less than about 6.0 μl / mg.
13. A lithium sulfur battery according to claim 11 or claim 12, wherein the ratio of electrolyte volume to sulfur weight is from about 3.5 μl / mg to about 5.0 μl / mg.
14. The sulfur cathode of any one of claims 1 to 10 or the lithium-sulfur battery of any one of claims 11 to 13, wherein the plurality of anion-functionalized cellulose nanofibers have a fibril diameter of about 0.5 nm to about 10 nm, or about 1 nm to about 6 nm, about 2 nm to about 4 nm.
15. The sulfur cathode of any one of claims 1 to 10 or 14 or the lithium-sulfur battery of any one of claims 11 to 14, wherein the plurality of anion-functionalized cellulose nanofibers have a fibril length of about 40 nm to about 700 nm, or about 70 nm to about 500 nm, or about 100 nm to about 400 nm.
16. The sulfur cathode of any one of claims 1 to 10, 14 or 15 or the lithium-sulfur battery of any one of claims 11 to 15, wherein the plurality of anion-functionalized cellulose nanofibers have a fibril aspect ratio of about 15 to about 750, or about 20 to about 500, or about 25 to about 200.
17. The sulfur cathode of any one of claims 1 to 10 or 14 to 16 or the lithium sulfur battery of any one of claims 11 to 16, wherein the zeta potential of the plurality of anion-functionalized cellulose nanofibers is from about -60 mV to about -90 mV.
18. The sulfur cathode of any one of claims 1 to 10 or 14 to 17 or the lithium sulfur battery of any one of claims 11 to 17, wherein the plurality of anion-functionalized cellulose nanofibers are functionalized to have one or more of: carboxyl, phosphonate, sulfonate, sulfate, hydroxyl, nitrate, and carbonate.
19. The sulfur cathode of any one of claims 1 to 10 or 14 to 18 or the lithium sulfur battery of any one of claims 11 to 18, wherein the plurality of anion-functionalized cellulose nanofibers comprises greater than 1 mmol anionic groups per gram of nanofibers or greater than 1.5 mmol anionic groups per gram of nanofibers.
20. The sulfur cathode of any one of claims 1 to 10 or 14 to 19 or the lithium-sulfur battery of any one of claims 11 to 19, wherein the plurality of anion-functionalized cellulose nanofibers comprises from about 1 mmol to about 4 mmol anionic groups per gram of nanofibers, or from about 1.5 mmol to about 4 mmol anionic groups per gram of nanofibers, or from about 2 mmol to about 4 mmol anionic groups per gram of nanofibers.
21. The sulfur cathode of any one of claims 1 to 10 or 14 to 20 or the lithium sulfur battery of any one of claims 11 to 20, wherein the plurality of anion-functionalized cellulose nanofibers are functionalized to have carboxyl groups.
22. The lithium-sulfur battery of any one of claims 11 to 21, wherein the sulfur cathode facilitates transport of lithium ions across the cathode during charge or discharge.
23. The lithium sulfur battery of any one of claims 11 to 22, wherein the sulfur cathode retards transport of polysulfide ions across the cathode during charge or discharge.
24. A cathode slurry composition comprising: a) a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers; b) one or more sulfur-containing materials; c) one or more conductive materials; and d) Water.
25. The cathode slurry composition of claim 24, wherein the ratio of water to the combined weight of components a), b) and c) is from about 1 ml / g to about 40 ml / g or from about 3 ml / g to about 30 ml / g.
26. A cathode slurry composition according to claim 24 or claim 25, wherein the slurry density of 3 ml / g slurry is 0.01 s when measured in the temperature range of 20-25°C. -1 The viscosity at the shear rate is greater than about 1000 Pa.s.
27. A method of preparing a cathode slurry composition according to any one of claims 24 to 26, the method comprising the steps of mixing a cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers, one or more sulfur-containing materials, one or more conductive materials, and water.
28. The method of claim 27, wherein the cellulosic composition, the one or more sulfur-containing materials, and the one or more conductive materials are dry mixed prior to mixing with water.
29. A cellulose composition comprising a plurality of anionically functionalized cellulose nanofibers, the nanofibers having one or more of the following properties: a) a fibril diameter of about 0.1 nm to about 20 nm; b) a fibril length of about 20 nm to about 1000 nm; c) a fibril aspect ratio of about 10 to about 1000; and d) The zeta potential is more negative than about -60 mV.
30. A method for preparing the cellulose composition according to claim 29, the method comprising: a) treating a cellulose source with one or more agents capable of anionically functionalizing cellulose nanofibers; and b) subjecting the anionically functionalized cellulose nanofibers to shear conditions to reduce one or more fibril sizes.
31. The method of claim 30, wherein the reagent is an oxidizing agent.
32. The method of claim 30 or claim 31, wherein the shear conditions in step b) comprise agitating the aqueous mixture of anionically functionalized cellulose nanofibers.
33. The method according to any one of claims 30 to 32, wherein the shearing conditions in step b) comprise one or both of ultrasonic homogenization and high pressure homogenization of the aqueous mixture of the anionically functionalized cellulose nanofibers.